The Challenge of Merger Result Bank during the Global Economic Recession due to the Covid-19 Pandemic: Case Study of Indonesian Islamic Banks - Fahmy Akbar Idries; Anwarul Sholihin; Ibi Satibi (Global Review of Islamic Economics and Business, 2021)
Bank Syariah Indonesia (BSI) is a new entity resulting from the merger of Bank Syariah Mandiri, BNI Syariah, and BRI Syariah. BSI was inaugurated in February 2021 amid the global economic recession due to the Covid-19 pandemic. It has not much been explained about the fundamental data of the 3 banks that formed BSI when the recession occurred due to the Covid-19 hit. As a result, BSI's record of challenges during the global recession has not appeared much. The aim of the research is to map the challenges that BSI will face when the economic recession due to the pandemic has not ended. BSI's challenge notes are useful for BSI policymakers, so they can mitigate risks. A  qualitative method Miles-Huberman model is employed to analyze the data which is done through 3 stages: data reduction, data display, and verification or conclusion. Based on data analysis, BSI will face the challenges of slow deposit and financing growth, rising non-performing financing, declining net profit, and declining sukuk ratings.